Genome-Wide Identification and Characterization of GASA Gene Family in Nicotiana tabacum - Li, Zhaowu; Gao, Junping; Wang, Genhong; Wang, Shuaibin; Chen, Kai; Pu, Wenxuan; Wang, Yaofu; Xia, Qingyou; Fan, Xiaorong (Frontiers in Genetics, 2022)
The gibberellic acid stimulated Arabidopsis (GASA) gene family is critical for plant growth, development, and stress response. GASA gene family has been studied in various plant species, however, the GASA gene family in tobacco (Nicotiana tabacum) have not been characterized in detail. In this study, we identified 18 GASA genes in the tobacco genome, which were distributed to 13 chromosomes. All the proteins contained a conserved GASA domain and highly specific 12-cysteine residues at the C-terminus. Phylogenetic analysis divided the NtGASA genes into three well-conserved subfamilies. Synteny analysis suggested that tandem and segmental duplications played an important role in the expansion of the NtGASA gene family. Cis-elements analysis showed that NtGASA genes might influence different phytohormone and stress responses. Tissue expression analysis revealed that NtGASA genes displayed unique or distinct expression patterns in different tissues, suggesting their potential roles in plant growth and development. We also found that the expression of NtGASA genes were mostly regulated by abscisic and gibberellic acid, signifying their roles in the two phytohormone signaling pathways. Overall, these findings improve our understanding of NtGASA genes and provided useful information for further studies on their molecular functions.